Analisis kinerja perbankan syariah di Indonesia periode 2008-2017 - Najiatun Najiatun; Alvin Arifin; Ach. Zuhri; Nurlaily Wulandari (Faculty of Economics and Business Mulawarman University, 2021)
The study analyzes the performance of Islamic banking in Indonesia for the 2018-2017 period. The purpose of this study is to analyze the performance of a sharia banking institution in Indonesia for the 2018-2017 period, because the financial performance of a bank shows the condition and health of a sharia banking report. The data analysis used is panel data regression analysis which is a combination of time series data for the period 2008 - 2017 and cross-setion data consisting of Muamalat Syariah, BNI Syariah, BRI Syariah, Maybank Syariah, Mega Syariah, BCA Syariah. The findings of this study are that the CAR and NIM variables partially have no significant effect on the performance of Islamic banks (ROA). And for the NPF and FDR variables partially have a significant effect on bank performance (ROA). Suggestions that can be given are the ratio of Islamic Bank's capital (CAR) can be improved by increasing the quality of capital. This can be done by paying more attention to capital requirements for each credit expansion in Islamic banks, the quality of the NPL ratio can be improved by being more careful in lending to customers to reduce the number of bad and non-performing loans.